Boccia game simulator: Serious game adapted for people with disabilities - Faria, Brigida Monica (2019)
Integration in the world of sport is one way for individuals with disabilities or motor disorders to feel more socially integrated, independent, and confident. Boccia is a Paralympic sport, which is increasingly getting more attention around the world. These facts have contributed to the objectives of this work. Including it in the serious games category enables to develop and rehabilitate the cognitive capabilities. The main focus was BC3 classification athletes (users with limited motor characteristics that require the use of an assistive device—a ramp, in this case). This paper describes a realistic Boccia game simulator adapted for people with disabilities that integrates a set of features that includes real physics and social features. These features can be used to enhance the interest of nonpractitioners of the sport and to improve the training conditions. The official Boccia regulation was added to the design of the simulator. The usability and approximation to the reality of the simulator were tested and validated based on the tests performed and data collected via a survey of users with no motor or psychological disorders. Realism and usability rating was almost excellent, and good results were achieved at the assessment of the game experience.